(NmNOGOLETNQQ IZMEN^IWOSTX MAKROCIRKULQCIONNYH FAKTOROW KLIMATA (B/s - (NbAJDAL(B, (NmIHAIL hARLAMPIEWI^s; (NhANVINA(B, (Nd(B. (Ng(B.s ((NmOSKWA (B:s (NgIDROMETEOIZDAT(B. (NmOSKOWSKOE OTD(B-(NNIE(B,s, 1986)
(NbIBLIOGR(B. (NS(B. 98-102 (84 (NNAZW(B.)s
Keywords: (NaTMOSFERA (B- (NcIRKULQCIQs; (NkLIMAT (B- (NiZMENENIQs